Associations between emotional awareness deficits and somatic symptoms in a community and clinical populations: a cross-sectional study - Sunyoung Kang; Chun Il Park; Se Joo Kim; Jee In Kang (BMC Psychology)
Abstract Background Deficits in emotional awareness may contribute to the development and maintenance of somatic symptoms. This study explored emotional awareness deficits and their association with somatic symptoms among individuals with a high somatic symptom burden from an online community sample, as well as among patients with somatic symptom disorders. Methods Emotional awareness deficits were analyzed by comparing 77 individuals with a high somatic symptom burden and 129 individuals with a low somatic symptom burden from a community population (Study 1). The severity of somatic symptom burden was measured using the Somatic Symptom Scale-8, with scores of eight or higher classified as high. Deficits in emotional awareness in clinical somatic symptoms were examined by comparing 34 patients with somatic symptom disorders to 34 matched healthy controls (Study 2). Emotional awareness was assessed by evaluating alexithymia using the 20-Item Toronto Alexithymia Scale (TAS-20) and empathy using the Interpersonal Reactivity Index (IRI). Multivariate analysis of covariance (MANCOVA) was conducted to examine group differences in emotional awareness while controlling for potential covariates. Results After adjusting for covariates, the MANCOVA results in Study 1 revealed significantly higher scores on the Difficulty Identifying Feelings subscale of the TAS-20 and the Personal Distress subscale of the IRI among participants with a high somatic symptom burden. These findings were replicated in Study 2, where patients with somatic symptom disorders exhibited deficits comparable to those of healthy controls. Conclusions This study suggests that difficulties in emotional awareness are closely associated with somatic symptoms in both clinical and community populations. Interventions aimed at improving emotional awareness may alleviate the manifestations of somatic symptoms and prevent related functional impairments. Clinical trial number Not applicable.